Globalization and Quality Assurance in Panama - Svenson, Nanette (International Higher Education, 2009)
Higher education in the developing world has changed dramatically over the past two decades, mainly as a result of increasing globalization. The most impacting of these forces come from two directions: economic and political. How the two factors interact and the kind of system they produce depend largely upon the quality-assurance mechanisms implemented.